INDEKS VISUAL FURNITUR DAN ARSITEKTUR JENGKI BERBASIS DATA PRESEDEN ARSITEKTUR - Firman Mutaqin; Deny Willy Junaidy; Andriyanto Wibisono (Tesa Arsitektur, 2022)
AbstractThe history and development of architectural styles and furniture always advance concurrently. The changes that occurred in the architecture will be reflected in the furnishing and vice versa. The character similarities and connection between architecture and furniture are not just associated with the styles, but furniture and architecture also have concurrence in structure integration, colors, texture, fabrication process, and visual components. Moreover, the relation is also depicted in the Jengki buildings and furniture, which is one of the base styles for the aesthetic value of Indonesian post-independence design. However, even though both of them have a typically unique pattern, there is no basis regarding special characteristic that is a visual geometric element as the ground for the similarity of both design patterns. This topic is compelling to observe, especially in the visual features of Jengki architecture and furniture. This research attempted to analyze the visual elements and characteristics of Jengki's design artifacts using precedents analysis on Jengki-style buildings and furniture. The results showed that there are characteristics and general patterns of Jengki, which included specifications and visual characteristics, along with visual similarities between the two. Afterward, the data was compiled into a Jengki visual indexing database consisting of 36 images of Jengki visual geometric elements. The database can be used as a resource and guidance in interpreting and assessing the level of Jengki design style also a reference for designing Jengki-style furniture. Keywords: Architecture, Furniture, Jengki, PrecedentAbstrakSejarah dan perkembangan gaya arsitektur dan furnitur selalu berjalan beriringan. Perubahan yang terjadi pada arsitektur akan tercermin pada furnitur begitu juga sebaliknya. Kesamaan karakteristik dan hubungan antara arsitektur dan furnitur tidak hanya terkait pada gaya, lebih dari itu furnitur dan arsitektur memiliki keselarasan dalam integrasi struktur, warna, tekstur, proses fabrikasi, dan komponen visual. Hal tersebut juga tergambar pada bangunan dan furnitur jengki yang merupakan salah satu gaya yang menjadi dasar nilai estetika desain paska-kemerdekaan Indonesia. Keduanya memiliki pola ciri khas yang unik namun belum ada landasan mengenai ciri khusus berupa elemen geometri visual yang menjadi latar belakang kesamaan pola desain keduanya, hal ini sangat menarik untuk diamati terutama pada unsur visual arsitektur dan furnitur jengki. Studi ini mencoba menganalisis elemen visual dan ciri-ciri artefak desain Jengki menggunakan analisis preseden pada bangunan jengki dan dikomparasikan dengan ciri visual furnitur bergaya jengki. Hasil studi menunjukkan adanya karakteristik dan pola umum jengki yang mencakup spesifikasi dan ciri khas visualnya serta persamaan visual di antara keduanya. Kemudian disusun sebuah database indexing visual jengki yang terdiri dari 36 gambar elemen geometri visual jengki. Database Indeks visual tersebut dapat digunakan sebagai referensi dan panduan dalam menerjemahkan dan menilai tingkat gaya desain jengki dan referensi bagi perancangan produk furnitur bergaya jengki.Kata kunci: Arsitektur, Furnitur, Jengki, Preseden.